2016
DOI: 10.1016/j.jvir.2015.12.459
|View full text |Cite
|
Sign up to set email alerts
|

Wall suction–assisted image-guided thoracentesis: a safe alternative to evacuated bottles

Abstract: Purpose: Computed tomography (CT)-guided percutaneous core biopsy of intrathoracic lesions is a well-established, minimally invasive procedure. However, clinically significant resultant pneumthoraces do occur. We investigated whether the use of a desiccated polyethylene glycol hydrogel lung plug prevents clinically significant pneumothoraces requiring chest tube placement and admission. Materials: A HIPPA compliant IRB approved retrospective study was performed. From 6/2013 to 5/2014, 168 consecutive patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…There is the theoretical risk of re-expansion pulmonary edema with large volume thoracentesis in a short period of time. 8 Kim et al reported rates of 2.1 and 0.9% in vacuum bottle and wall suction groups, respectively, which were comparable to the reported incidences with conventional drainage systems of 0 to 2.7% suggesting no increased risk. 8 Hence, it is recommended to drain not more than 1 to 1.5L of fluid drainage per day.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…There is the theoretical risk of re-expansion pulmonary edema with large volume thoracentesis in a short period of time. 8 Kim et al reported rates of 2.1 and 0.9% in vacuum bottle and wall suction groups, respectively, which were comparable to the reported incidences with conventional drainage systems of 0 to 2.7% suggesting no increased risk. 8 Hence, it is recommended to drain not more than 1 to 1.5L of fluid drainage per day.…”
Section: Discussionmentioning
confidence: 62%
“…8 Kim et al reported rates of 2.1 and 0.9% in vacuum bottle and wall suction groups, respectively, which were comparable to the reported incidences with conventional drainage systems of 0 to 2.7% suggesting no increased risk. 8 Hence, it is recommended to drain not more than 1 to 1.5L of fluid drainage per day. 8 Our procedurists are aware of this complication when using the chest bottle and regularly provide this cautionary statement in the report, and recognition of this risk is reflected by the Privac system being favored for smaller volume collections in our study.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations